SQL Server 2016 developer's guide : get the most out of the rich development capabilities of SQL Server 2016 to build efficient database applications for your organization /: get the most out of the rich development capabilities of SQL Server 2016 to build efficient database applications for your organization. (2017) - Sarka, Dejan; Radivojević, Miloš; Durkin, William
No abstract available